The detailed priority of international freight expresses in the overlapping section of RFC 7 and RFC 9 Kolín – Choceň - Molková, Tatiana; Šrámek, Přemysl (České vysoké učení technické v Praze, 2017)
The main goal of this article is to research the optimal priority of international freight expresses, especially on European freight corridors. This article shows this problem in the context in the overlapping section of RFC 7 and RFC 9 Kolín – Choceň. There is solved changing priority of freight expresses in detail, whereas other train priorities are the same.
Priorita mezinárodní nákladní dopravy v překrývající se části RFC 7 a RFC 9 - Kolín - Choceň
Keywords: Capacity; freight expresses; freight corridors; timetable stability; Kapacita; nákladní expres; koridory nákladní dopravy; stabilita jízdního řádu